Nelson Mandela: the ripple effect - Maithufi, Sope (Third world quarterly, 2018)
This article considers how Nelson Mandela's immediate family members intellectualised themselves within his legacy when he was terminal and upon his death. These specifics sublimate and set him apart from the eulogising tendency such as it has energised the scholarship on him. The tactics highlight tradition as an analytical category. Citing succession as a key episteme, the discussion delineates how tradition rarefies in non-hegemonic, mobile and fragile subject positions. In this approach, the paper invokes subtleties in the African Customary Law of Succession in South Africa.